Seroprevalence and Molecular Detection of Human Parvovirus B19 in Beta Thalassemia Major Patients - Al-Musawe, Noor Thamir; Al-Malkey, Maysaa Kadhim (Iraqi Journal of Science, 2025)
Beta thalassemia major (BTM) is a genetic disorder that has been linked to an increased risk of contracting blood-borne viral infections, primarily due to the frequent blood transfusions required to manage the condition. One such virus that can be transmitted through blood is the Human Parvovirus B19 (B19V). The aim of this study was to investigate the frequency and molecular detection of B19V. This study included 60 blood donors as controls and 120 BTM patients. B19V was identified by serology, which measured B19-IgG and B19-IgM antibodies. Nested Polymerase Chain Reaction (nPCR) was employed to target the VP1/VP2 structural proteins. The results showed that B19V seropositivity represents 27.5% (33 out of 120) in BTM patients, and only 8 out of 60 subjects represents (13.3%) in the control group (P-value 0.078). Notably, male patients exhibited a significantly higher prevalence of B19-IgM and B19-IgG antibodies, with 32% and 24% of males testing positive, respectively, compared to female patients. Elevated levels of Aspartate and Alanine Transaminase were observed with values of 51.94±50.09 and 46.81±50.20, respectively. Additionally, nPCR analysis detected B19V DNA in 4.16% (5 out of 120) of BTM patients, while no positive results were detected in the control group. Screening the blood and blood products for the virus in high-risk group can considerably reduce the prevalence. Preventive measures are required in such vulnerable population.